Characterization Of The Main Character In The Movie 12 Angry Man - Marbun, Jonathan; Girsang, Martina; Butar-Butar, Justin Hubert; Sembiring, Reja Ananda; Hadi, Muhammad Nur (Lembaga Riset dan Inovasi Almatani, 2025)
The research described character of 12 angry man movie directed by Sidney Lumen adapted from teleply by Reginald Rose,. The purpose of this research was to analyze the psychological theory benefits of the main character such as unconscious mind, character analysis, symbolism also to find the dominant data of the main character’s personality. In the writing of this research, the researcher used qualitative research method. The researcher used the theory of Freud’s theories to analyze the psychological theory. The researcher collected the data from 12 Angry Men movie as a primary data. Then for the secondary data sources from books, internet, journal, that is relevance to strengthen the argument. The data collection in this research was done by watching movie and took notes before did the analysis from dialogue, situation that delivered in the movie which becomes the main data of this research. In result of this research, the researcher found that the main character, Henry Fonda as a Mr. Davis, depicted has individual and social attitudes.